Molecular Epidemiology of Mycobacterium tuberculosis strains isolated from pulmonary tuberculosis patients in south Ethiopia - Yared Merid; Elena Hailu; Getnet Habtamu; Melaku Tilahun; Markos Abebe; Mesay Hailu; Tsegaye Hailu; Daniel Gemechu Datiko; Yimtubezinash Woldeamanuel; Abraham Aseffa (Journal of Infection in Developing Countries)
Introduction: Understanding the epidemiology of tuberculosis is limited by lack of genotyping data. We sought to characterize the drug susceptibility testing patterns and genetic diversity of M. tuberculosis isolates in southern Ethiopia.